IMMUNOHISTOCHEMICAL STUDY OF DEPIGMENTED SKIN OF VITILIGO PATIENTS - Revishchin, A V; Panteleev, D Yu; Zakharova, L G; Lomonosov, K M; Pavlova, G V (T͡S︡itologii͡a, 2017)
Immunohistochemical analysis was used to study depigmented skin areas such as macular of depigmentation and skin perimakular areas in vitiligo patients. It has been shown that the cells containing melanocytic cell marker TRP1 are localized both in macular and perimakular areas. Within the macula of depigmentation all TRP1 positive cells are in close contact with the basement membrane. In perimakular areas many cells that have lost contact with the basement membrane, were localized deep in the epidermis. About 92 % of TRP1 positive perimakular cells were also vimentin positive. Vimentin positive cells were numerous in perimakular areas but missing in the macula of depigmentation. Dense groups of cells immunopositive for transcription factor Snail, known as inductor of epithelial-mesenchymal transition, were localized in perimakular areas in close proximity to the macula depigmentation border. Such cells were extremely rare within the macula of depigmentation. There is reason to assume that an intensive process, which is similar to the epithelial-mesenchymal transition, might be the cause of melanocyte death in perimakular field, and thus prevents repigmentation of depigmented areas.